Social Mobility and Demand for Redistribution. A Comparative Analysis - Jaime-Castillo, Antonio Manuel; Marqués-Perales, Ildefonso (My University, 2016)
The literature on preferences for redistribution has paid little attention to the effect of social mobility on the demand for redistribution, which is in contrast with the literature on class-voting, where studies on the effect of social mobility has been very common. Some works have addressed this issue but no systematic test of the hypotheses connecting social mobility and preferences has been done. In this paper we use the diagonal reference models to estimate the effect of origin and destination class on preferences for redistribution in a sample of European countries using data from the European Social Survey. Our findings indicate that social origin matters to a little extent to explain preferences, as newcomers tend to adopt the preferences of the destination class. Moreover, we have found only limited evidence supporting the acculturation hypothesis and not support for the status maximization hypothesis. Furthermore, the effect of social origin varies largely between countries. In a second step of the analysis we investigate what are the national factors explaining this variation. The empirical evidence we present leads to conclude that high rates of upward social mobility sharply reduce the effect of social origin on preferences for redistribution
Keywords: Movilidad social